Badiou and indifferent being : a critical introduction to Being and event - Watkin, William, 1970- (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2017)
"This in depth exploration is the first part of a two part study of the two volumes of Alain Badiou's seminal Being and Event project. Badiou and Indifferent Being is an original, systematic study of Being and Event that takes into consideration the dramatic modifications to Badiou's philosophy since the publication of Logics of Worlds (2006). In that central elements of Badiou's philosophy, such as the situation, the event and the subject, are incomplete in Being and Event, this is the only fully up-to-date and accurate consideration of Badiou's overall philosophy yet published. At the same time as presenting an up-to-date account of Badiou's overall philosophy, the book is the first to draw out the central component of Badiou's ontology namely its relation to the category of indifference. Concentrating on the use of indifference across all the core elements of ontology, in particular the void, the pure multiple, the concept of set and the event, the book demonstrates that because set theory as such is a mathematics of indifference and for Badiou ontology is mathematics, no account of Badiou's ontology is complete unless it accepts that Badiou's theory of being is a presentation of indifferent being. The book provides a detailed and lively section by section reading of Badiou's foundational work, presenting all his concepts for all Badiou readers from undergraduates to researchers. It is a seminal source text for all future readings of Badiou."--Bloomsbury Publishing